Formulação de pastas cimentícias com adição de suspensões de quitosana para cimentação de poços de petróleo - Nobrega, Andreza Kelly Costa (2009)
Primary cementing is one of the main operations in well drilling responsible for the mechanical stability and zonal isolation during the production of oil. However, the cement sheath is constantly under mechanical stresses and temperature variations caused by the recovery of heavy oil. In order to minimize fracture and wear of the cement sheath, new admixtures are developed to improve the properties of Portland cement slurries and avoid environmental contamination caused by leaking gas and oil. Polymers with the ability to form polymeric films are candidates to improve the properties of hardened cement slurries, especially their fracture energy. The present study aimed at evaluating the effect of the addition of a chitosan suspension on cement slurries in order to improve the properties of the cement and increase its performance on heavy oil recovery. Chitosan was dissolved in acetic ac id (0.25 M and 2 M) and added to the formulation of the slurries in different concentrations. SEM analyses confirmed the formation of polymeric films in the cementitious matrix. Strength tests showed higher fracture energy compared to slurries without the addition of chitosan. The formation of the polymeric films also reduced the permeability of the slurry. Therefore, chitosan suspensions can be potentially used as cementing admixtures for heavy oil well applications